Comparative study between fentanyl and dexmedetomidine as adjuvant to ropivacaine in supraclavicular brachial plexus block: A prospective and randomized study - Banerjee, Siddhi; Halder, Susanta Kumar; Banerjee, Tibar; Das, Debojyoti; Biswas, Rajdeep; Chakraborty, Soma; Saha, Debasish (Asian Journal of Medical Sciences, 2024)
Background: Supraclavicular brachial plexus block (BPB) is being utilized extensively for upper limb surgeries. To improve block quality, several adjuvants have been used successfully. Fentanyl and dexmedetomidine has been evaluated as adjuvants for such block done using ropivacaine. However, block qualities have been modified to a variable extent with use of such adjuvants. Aims and Objectives: Hence, the study was designed to compare fentanyl and dexmedetomidine as adjuvants during ropivacaine-induced supraclavicular BPB. Materials and Methods: Sixty adults undergoing upper limb surgeries were randomly divided in to two groups to receive either fentanyl or dexmedetomidine as adjuvants to ropivacaine for supraclavicular BPB. The onset of sensory block was the primary outcome measure. Duration of sensory bloc, motor block characteristics, and adverse events were also evaluated. Results: Considerably faster onset of sensory and motor blockade was found with the use of fentanyl as adjuvant over dexmedetomidine (sensory, 8.2±1.19 vs. 12.07±0.96, P<0.001; and motor, 7.0±0.43 vs. 30.43±1.41, P<0.001). However, the duration of sensory and motor blockade were found considerably prolonged with the use of fentanyl over dexmedetomidine. Conclusion: Fentanyl can be a better alternative to dexmedetomidine as adjuvant to ropivacaine for supraclavicular BPB in view of faster onset of sensory and motor block. While prolonged duration of sensory block appears to be beneficial, the prolonged motor block can cause delay patient mobility.